Comparative analysis of strategies to prepare electron sinks in aquatic photoautotrophs - Shimakawa, Ginga; Murakami, Akio; Niwa, Kyosuke; Matsuda, Yusuke; Wada, Ayumi; Miyake, Chikahiro (Photosynthesis research, 2019)
While subject to illumination, photosystem I (PSI) has the potential to produce reactive oxygen species (ROS) that can cause photo-oxidative damage in oxygenic photoautotrophs. The reaction center chlorophyll in PSI (P700) is kept oxidized in excess light conditions to limit over-excitation of PSI and alleviate the production of ROS. Oxidation of P700 requires a sufficient electron sink for PSI, which is responsible for flavodiiron proteins (FLV) safely dissipating electrons to O 2 in cyanobacteria, green algae, and land plants except for angiosperms during short-pulse light (SP) illumination under which photosynthesis and photorespiration do not occur. This fact implies that O 2 usage is essential for P700 oxidation but also raises the question why angiosperms lost FLV. Here, we first found that aquatic photoautotrophs in red plastid lineage, in which no gene for FLV has been found, could keep P700 oxidized during SP illumination alleviating the photo-oxidative damage in PSI even without O 2 usage. We comprehensively assessed P700 oxidation during SP illumination in the presence and absence of O 2 in cyanobacteria (Cyanophyta), green algae (Chlorophyta), angiosperms (Streptophyta), red algae (Rhodophyta), and secondary algae (Cryptophyta, Haptophyta, and Heterokontophyta). A variety of dependencies of P700 oxidation on O 2 among these photoautotrophs clearly suggest that O 2 usage and FLV are not universally required to oxidize P700 for protecting PSI against ROS damage. Our results expand the understanding of the diverse strategies taken by oxygenic photoautotrophs to oxidize P700 and mitigate the risks of ROS.